CATCH ANALYSIS IN 1974 AND FBHING TRENDS IN THE JAISAMAND LAKE (RAJASTHAN) - Durve, V S; Kakkar, Virendra (Indian Journal of Fisheries, 2011)
The lake Jaisamand, one of the most productive lakes in India, is situated southeast of Udaipur. The lake has been in existence for more than the last 250 years. In spite of indiscriminate exploitation, without observing closed season till 1970 atid any restriction on the mesh-size, and without stocking, this supported a sizable fishery since 1949